Parkrun an organised running revolution - Hindley, David (New York : Routledge, 2022)
This is the first book to take an in-depth look at parkrun - the free, weekly, timed 5km run on a Saturday morning - and to examine why its participants love it so much and why it has been such an astonishing success. Author David Hindley - a self-described middle of the pack' parkrunner - draws on new research, including interviews with other runners, volunteers and organisers, to shine a light on the unique combination of ingredients in parkrun's magic formula. Tracing the development of parkrun from its first event in the UK in 2004 to the global network of today, he takes a close look at themes like inclusion, volunteering, community, green space, health and well-being, and unpacks the mantra of it's a run not a race' that has come to define the spirit of parkrun for so many of its participants. Part sporting event, part social movement, and part public health intervention, parkrun perhaps offers a model for sustainable public participation in other areas of social life. This book is compulsory behind-the-scenes reading for all parkrunners and parkrun volunteers, and anybody working in sport development, events, recreation, public health, volunteering or community organising.
Keywords: Parkruns; Outdoor recreation; Community life; SPORTS & RECREATION / Sociology of Sports; SPORTS & RECREATION / Running & Jogging